Presentation of Key Findings from a Study on Political Interventions and Clientelism in the Work of Public Administration in the Case of Water Resource Management by Local Government Authorities - Karagianni, Grammatoula (HAPSc Policy Briefs Series, 2024)
Public Administration undergoes numerous changes in its mission to serve citizens. Sometimes, these changes are influenced by political interventions aimed at showcasing their social responsibility, particularly highlighting public policy, which is often confined within the narrow bounds of political decisions. Moreover, corruption and clientelism are phenomena associated with the exercise of public policy. This policy brief presents some key findings from postdoctoral research, which conducted from 2013 until 2020, on these issues in the case of the Region and Municipalities of Northern Greece regarding water resource management. The research concludes that there are issues of clientelism and that political interventions affecting the implementation of legislation were absent.